An Assessment of Teachers’ Competency and Students’ Preparedness in STEM Education: The Case of Ilocos Norte Public Secondary Schools - Glaiza Amor O. Guillermo; Lilibeth G. Abrogena (Future Science / FSH-PH Publications, 2026)
This study examined the level of teacher competency and student preparedness in Science, Technology, Engineering, and Mathematics (STEM) education in the Schools Division of Ilocos Norte. A descriptive research design was employed using total enumeration of all 99 STEM teachers handling Science, Mathematics, and Technology-related subjects in the 32 public secondary schools offering the STEM strand. Data collection was conducted during the first two months of the second semester of School Year 2025–2026, allowing assessment after the completion of first-semester requirements and alignment with recent 2025 educational literature. Data were gathered through adapted survey instruments consisting of Teacher Competency Checklist and Student Preparedness Checklist, both utilizing a 4-point Likert scale. The instruments were teacher-rated; both teacher competency and student preparedness were assessed based on teachers’ perceptions. Quantitative data were analyzed using weighted mean and descriptive interpretation. Results showed that STEM teachers perceived themselves as very highly competent, with the highest ratings in the domains of classroom instruction and content and pedagogy, and as highly competent in the domain of qualification and training. Students are highly prepared in STEM education, as perceived by teachers in terms of academic knowledge, laboratory and technological skills, as well as attitude and study habits. The findings of this study are consistent with inquiry-based and social constructivist theories emphasizing learner-centered instruction and collaborative problem solving. The very high teacher ratings in hands-on learning, open-ended inquiry, and differentiated classroom strategies reflect recommended pedagogical practices.